THE EFFECT OF RAWS MATERIALS OF CATFISH (Pangasius Hypopthalmus) AND SNAKEHEAD FISH SURIMI (Channa Striata) TOWARD FISHBALL QUALITY FOR COLD TEMPERATURE STORAGE - Aimin, Mul; Loekman, Suardi; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study was aimed to determine the quality of fishball was processed from raw material of surimi in organoleptic, proximate and microbiology for cold storage. The method used was experimental method with a random group non factorial (RAK), with three level treatment i.e surimi of catfish (B1), surimi of snakehead (B2) and mixture of surimi catfish and snakehead (B3) for 0,15,30 days of storage. The parameters in this research was organoleptic (appearance, aroma, flavor and texture), proximate analyses (water, protein and fat content) and microbiology (total bacterial colonies). The result showed that raw material of surimi was significant affect to organoleptic value, proximate and microbiology. The best treatment was the mixture catfish surimi and snakehead surimi (B3) with organoleptic value of appereance (8), aroma (7), flavor (8) and texture (8), proximate value of water content (45,49%), protein (28,18%) and fat content (2,15%), the total of bacterial colony was 3,9x103 CFU/grKey word : surimi, storage, fish ball, temperature cold